Pengembangan Buku Ajar Kimia Kelas X Berbasis Reduksi Didaktik: Uji Kelayakan di SMA Negeri Kota Banjarmasin - Arif Sholahuddin (Jurnal Pendidikan dan Kebudayaan, 2011)
This first phase of research and development is to produce chemistry instructional book for class X based on reduction-didactic which is feasible used in teaching and learning. The sample, three schools of 13 State Senior High Schools of Banjarmasin, are drawn using stratified random sampling. The collected research datas are analyzed descriptively based on instructional book feasibility indicators, where instructional book is considered as a feasible book for teaching and learning if both validation and student’s responses score to it in good or very good category; classically, 80% of students or more achieve mastery level of > 65. This research show that the instructional book is feasible because it’s validity is very good, student’s responses is good and classically, students’ mastery level reaches 80.2%. Futhermore, in order to increase more qualified instructional book and students’ mastery level, hence it’s need to increase the student’s self-learning; to direct students to follow the instructional book guidelines, to conduct futher field test that involve a wide range of samples and develop it as an interactive instructional book. ABSTRAK Penelitian dengan desain Research and Development tahap pertama ini bertujuan untuk menghasilkan buku ajar kimia kelas X berbasis reduksi didaktik yang layak digunakan dalam pembelajaran. Sampel diambil secara stratified random sampling sebanyak 3 sekolah dari 13 SMA Negeri di Banjarmasin. Data penelitian dianalisis secara deskriptif berdasarkan indikator kelayakan yaitu buku ajar dianggap layak jika skor validasi maupun respon siswa terhadap buku ajar dalam kategori baik atau sangat baik dan sebanyak 80% atau lebih siswa mencapai tingkat penguasaan >65. Hasil penelitian menunjukkan bahwa buku ajar layak digunakan karena validitas buku ajar dalam kategori sangat baik, respon siswa terhadap buku ajar dalam kategori baik dan ketuntasan belajar siswa secara klasikal mencapai 80,2%. Selanjutnya untuk meningkatkan kualitas buku ajar dan tingkat penguasaan siswa, guru perlu meningkatkan kemandirian belajar siswa, membimbing siswa agar mengikuti panduan penggunaan buku, melakukan ujicoba lanjut yang melibatkan sampel lebih luas dan mengembangkannya menjadi buku ajar interaktif.